2013
DOI: 10.3233/dev-1312112
|View full text |Cite
|
Sign up to set email alerts
|

Ostracism and Children: A Guide to Effectively Using the Cyberball Paradigm With a Child Sample

Abstract: Ostracism, the act of being excluded or ignored by another individual or group (Williams, 1997;Williams et al., 2002), is a powerful, pervasive, and complex phenomenon that transcends time and affects individuals throughout their lifespan, with some of the most damaging exclusionary experiences occurring during childhood (Williams, Forgas, & von Hippel, 2005). The current paper: a) discusses some of the problems associated with empirically investigating ostracism with a child sample using the widely used and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…The Cyberball paradigm was used with minor adjustments (see Williams & Jarvis, ; Zadro et al, ). Children played against three pre‐programmed players, depicted by animated figures and labeled as Player 1, Player 2, and Player 3 on the screen.…”
Section: Methodsmentioning
confidence: 99%
“…The Cyberball paradigm was used with minor adjustments (see Williams & Jarvis, ; Zadro et al, ). Children played against three pre‐programmed players, depicted by animated figures and labeled as Player 1, Player 2, and Player 3 on the screen.…”
Section: Methodsmentioning
confidence: 99%
“…Further research with children has also indicated adequate internal consistency for this measure (Hawes et al, 2012; that is comparable to the adult version of the scale (Williams et al, 2002). The internal consistency for total need threat for this sample was slightly higher than that reported by Zadro et al (2013), with an alpha of .87, M = 33.61, SD = 7.44. Spearman-Brown coefficients were calculated for the individual needs, as this statistic has been found to be most appropriate for two-item scales (Eisinga, Grotenhuis, & Pelzer, 2013).…”
Section: Zadro Et Al (2013) Reported Internal Consistency For This Mmentioning
confidence: 61%
“…As shown in Table 4, internal consistency coefficients for this sample were slightly higher for meaningful existence and control, and slightly lower for self-esteem and belonging, as compared to Zadro et al (2013). Resource Allocation.…”
Section: Zadro Et Al (2013) Reported Internal Consistency For This Mmentioning
confidence: 71%
See 2 more Smart Citations